IMPLEMENTASI PEMELIHARAAN LAHAN BUDIDAYA UBIKAYU MELALUI PERBAIKAN DAN MONITORING KUALITAS TANAH - Nurul Muddarisna; Sugeng Priyono (BUANA SAINS, 2009)
A field experiment that was amied to elucidate the effects of application of Arachis pintoi biomass and farmyard manures on soil quality and cassava yield was conducted at Jatikerto Village, Kromengan District of Malang Regency. Eight treatments tested were 100% NPK inorganic fertilizer, 100 kg N Arachis pintoi/ha (PH), (3) 100 kg N chicken farmyard manure/ ha (PA), 100 kg N cow farmyard manure /ha (PS), 100 kg N goat farmyard manure /ha (PK), 100 kg N Arachis pintoi + chicken farmyard manure /ha (PH+PA), 100 kg N Arachis pintoi + cow farmyard manure /ha (PH+PS), and 100 kg N Arachis pintoi + goat farmyard manure /ha (PH + PK). Monitoring of top soil quality (0-20 cm depth) was carried out before planting and 3 months after planting. Soil samples were collected and analyzed for bulk density, porosity, aggregate stability, soil permeability, pH, organic-C, humic acid, nitrogen, phosphorus, potassium, cation exchange capacity, microbial population and nitrogen microbial biomass. Yield of cassava that was based on the number of tuber per plant, was measured at 6 months after planting. Results of this study showed that application of organic fertilizer in forms of green manure (Arachis pintoi biomass), and farmyard manures significantly improved soil parameters. Application of 50% NPK combined with organic manures did not significantly gave different tuber yield with that of 100% NPK